A Randomized Trial of the Effects of Nebulized Albuterol on Pulmonary Edema in Brain‐Dead Organ Donors. Issue 3 (24th January 2014) - Ware, L. B.; Landeck, M.; Koyama, T.; Zhao, Z.; Singer, J.; Kern, R.; Neidlinger, N.; Nguyen, J.; Johnson, E.; Janz, D. R.; Bernard, G. R.; Lee, J. W.; et al.
<x xml:space="preserve">Abstract</x> Donor lung utilization rates are persistently low primarily due to donor lung dysfunction. We hypothesized that a treatment that enhances the resolution of pulmonary edema by stimulating the rate of alveolar fluid clearance would improve donor oxygenation and increase donor lung utilization. We conducted a randomized, blinded, placebo‐controlled trial of aerosolized albuterol (5 mg q4h) versus saline placebo during active donor management in 506 organ donors. The primary outcome was change in oxygenation arterial partial pressure of oxygen/fraction of inspired oxygen [PaO2/FiO2] from enrollment to organ procurement. The albuterol (n = 260) and placebo (n = 246) groups were well matched for age, gender, ethnicity, smoking, and cause of brain death. The change in PaO2/FiO2 from enrollment to organ procurement did not differ between treatment groups (p = 0.54) nor did donor lung utilization (albuterol 29% vs. placebo 32%, p = 0.44). Donors in the albuterol versus placebo groups were more likely to have the study drug dose reduced (13% vs. 1%, p < 0.001) or stopped (8% vs. 0%, p < 0.001) for tachycardia. In summary, treatment with high dose inhaled albuterol during the donor management period did not improve donor oxygenation or increase donor lung utilization but did cause tachycardia. High dose aerosolized albuterol should not be used in donors to enhance the resolution of pulmonary edema.